Research into student understanding within university courses: A commentary on the last three papers - Lindblom - Ylanne, Sari (Psychology: the Journal of the Hellenic Psychological Society, 2020)
This commentary looks at the last three articles on the special issue, those by Velda McCune, Evangelia Karagiannopoulou and Sue Hallam and Hazel Francis. The first two papers focus on exploring students’ understanding. Velda McCune explores learner identities and the will to understand of undergraduate bioscience students. Evagelia Karagiannopoulou analyses the effect of in-class experiences and the nature of examinations on understanding of final-year psychology students. The third paper by Sue Hallam and Hazel Francis deals indirectly with understanding and focuses on analysing students’ conceptions of the nature of argument. Skills of argumentation are a crucial part of critical thinking skills which, in turn, have been shown to be related to the deep approach to learning.